Addressing the unmet needs in patients with type 2 inflammatory diseases: when quality of life can make a difference - Gómez de la Fuente, Enrique; Alobid, Isam; Ojanguren, Iñigo; Rodríguez-Vázquez, Virginia; Pais, Beatriz; Reyes, Víctor; Espinosa, Miriam; Luca de Tena, África; Muerza, Irantzu; Vidal-Barraquer, Eduard (Frontiers in Allergy, 2023)
This study delves into the shared experiences of patients grappling with various Type 2 inflammation (T2i) related diseases, including asthma, atopic dermatitis, allergic rhinitis, and more. These conditions share a common underlying cause—Type 2 inflammation, which often coexists with other T2i disorders and significantly impacts patients' quality of life (QoL). Despite the evident importance of understanding these diseases from the patient's perspective, limited data has been available on their experiences, viewpoints, and the current management of T2i diseases within a unified framework. In response, the patient-driven T2i Network Project initiated a comprehensive survey designed to illuminate the collective challenges and drivers influencing the QoL of patients dealing with T2i diseases. This survey, conducted anonymously online between May and June 2023, featured the collaboration of various stakeholders, including patient associations, healthcare professionals, and healthcare quality experts. A total of 404 participants, predominantly experiencing moderate-to-severe self-reported disease severity (93%), took part in the survey. Importantly, a majority (59%) reported having multiple coexisting pathologies linked to T2i. The impact on QoL was notably more severe for patients contending with multiple pathologies, as compared to those with only one (p<.001). Additionally, participants with self-reported severe symptoms exhibited significantly worse QoL compared to their mild-to-moderate counterparts (p<.001). A key finding revealed that over half of the patients (56%) grappled with the constant anxiety stemming from the unpredictability of their illnesses, often triggered by known or unknown factors. This patient-led initiative offers crucial insights into the shared QoL challenges faced by individuals affected by T2i-related diseases. It underscores the pressing need for further research aimed at enhancing the management of this patient group. Given the substantial impact on QoL, the study advocates for a multidisciplinary approach integrated into new healthcare protocols, with the potential to improve patient management, expedite diagnoses, and reduce healthcare resource utilization. These findings align closely with the focus of journals dedicated to understanding the underlying mechanisms of allergic conditions, as they shed light on the common pathogenesis and challenges experienced by patients in managing T2i-related diseases.